2010
DOI: 10.1128/jvi.00505-10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clade-Specific Sequence Polymorphisms on HIV-1 Protease Activity and Inhibitor Resistance Pathways

Abstract: The majority of HIV-1 infections around the world result from non-B clade HIV-1 strains. The CRF01_AE (AE) strain is seen principally in Southeast Asia. AE protease differs by ϳ10% in amino acid sequence from clade B protease and carries several naturally occurring polymorphisms that are associated with drug resistance in clade B. AE protease has been observed to develop resistance through a nonactive-site N88S mutation in response to nelfinavir (NFV) therapy, whereas clade B protease develops both the active-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Our inhibitor-bound co-crystal structures revealed that the N88D secondary mutation interacts with residue 30 to orient the side chain away from the active site (20) and thereby disrupts the interaction between residue 30 and the inhibitor. This effect is even more pronounced in subtype AE, where N88S pulls D30 out of the active site (21). We also showed that D30 not only is key for inhibitor binding but also is essential for recognition of the p1-p6 cleavage site (8,15,22).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 64%
“…Our inhibitor-bound co-crystal structures revealed that the N88D secondary mutation interacts with residue 30 to orient the side chain away from the active site (20) and thereby disrupts the interaction between residue 30 and the inhibitor. This effect is even more pronounced in subtype AE, where N88S pulls D30 out of the active site (21). We also showed that D30 not only is key for inhibitor binding but also is essential for recognition of the p1-p6 cleavage site (8,15,22).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 64%
“…Only subtle differences in the hydrophobic core are evident between the crystal structures of the subtype B and C-SA proteases. Similarly, the HIV-1 A_E variant, which has polymorphisms in the hydrophobic core, does not display major structural differences in this region relative to the subtype B protease [53]. Analysis of the dynamics of the hydrophobic core is limited because residues in the core are disconnected in the primary structure of the HIV-1 protease.…”
Section: Effect Of Secondary Resistance Mutations On Flap Movementmentioning
confidence: 99%
“…Slow exchange is expected here due to low solvent accessibility and a complex network of interactions around the active-site core. The flap tips (residues at positions [49][50][51][52][53] are the regions of the proteases that display the fastest deuterium incorporation. The flaps are completely solvent-exposed and highly mobile.…”
Section: Dynamics Of the Hiv-1 Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the formation of a homo-dimer in which each monomer consists of 99 amino residues, the mature HIV-1 protease is produced through processing of the precursor peptide in the viral particle. Polymorphisms are frequently observed, 10,11) and about 500000 sequences have been registered in the Los Alamos HIV database. 12) Polymorphism and/or amino acid mutation have a close relation with the emergence of drug resistance.…”
mentioning
confidence: 99%